Trade in torture tools threatens detainees and protestors everywhere – it must be banned - Edwards, Alice Jill (Torture Journal, 2024)
With social upheaval, economic strain, and political unrest growing, peaceful demonstrations worldwide are increasingly met with brutal tactics by law enforcement and security forces. The UN Special Rapporteur on Torture outlines her call for States to negotiate a new international treaty to ban the manufacture, use and trade in “torture tools” and regulate the trade in law enforcement equipment. Her proposal outlines two critical components: a Prohibited list of items that she has deemed to be inherently cruel, inhuman or degrading, and a second Controlled list of ordinary law enforcement equipment that has a high risk of misuse. Effective international regulation is imperative to curb the indiscriminate use of force by law enforcement and to uphold human dignity. Improved national regulation is also required. Her research has revealed a pervasive market for these items, with more than 335 companies in 54 countries manufacturing or promoting the most egregious torture instruments. Major producers include China, the EU, and the USA, with emerging economies also contributing significantly. The outsourcing of public functions to private security companies further exacerbates the issue, underscoring the pressing need for robust national and international regulations.